Pemberdayaan Masyarakat dalam Pemanfaatan Limbah Cangkang Rajungan Menjadi Pupuk Organik Cair Melalui Kegiatan Kkn di Desa Aengdake - Sabrina Husnatin P; Nur Lailia I; Hera Laras Trinita N; Emi Firda A (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
This community outreach and training activity aims to enhance the utilization of crab shell waste into an environmentally friendly and economically valuable product through the production of liquid organic fertilizer (LOF) in Aeng Dake Village. Crab shell waste, previously considered as environmental pollution, was processed through a fermentation process lasting 14–21 days. The results indicate increased community awareness of environmentally based waste management and successful production of liquid organic fertilizer rich in nutrients and chitin, which improves soil fertility and reduces dependence on chemical fertilizers. The use of audiovisual media proved effective in improving community understanding and supporting program sustainability. Furthermore, this activity creates new economic opportunities for local communities. Therefore, the utilization of crab shell waste has significant potential to support environmental sustainability and the economic development of coastal communities.